(untitled) (Research, Society and Development, 2021)
Solar radiation is a vital energy source for all biological, chemical, physical and atmospheric processes. In addition, nowadays, with a growing concern in relation to the use of alternative and sustainable sources of energy, its use has been used as a good solution for energy conversion, water temperature control and thermal comfort. For each place where the use of solar radiation will be made, it is necessary to know the annual variation of the quantitative energy levels incident, because in each region of the planet, the behavior of the incident global solar radiation presents different annual variations. When working on a sloping surface, the orientation and angle of the slope of the surface changes the energy levels received when compared to a horizontal surface. Measures of solar radiation on an inclined plane are not common in meteorological stations due to financial, instrumentation and operating barriers. For this reason, the energetic and thermal potential of solar radiation on a vertical surface is neglected. This work aimed to evaluate the global solar irradiation data on a vertical surface oriented to the North measured during 2010 at the radiometry station of the Rural Engineering Department of the Faculty of Agronomic Sciences at UNESP in Botucatu. Classical literature models were tested to estimate global irradiation developed on inclined surfaces and were compared with data from the Botucatu-SP radiometry station measured on a vertical surface. In the end, a model for estimating the global solar irradiation for vertical surface was proposed for Botucatu-SP.